Beta cell function after intensive subcutaneous insulin therapy or intravenous insulin infusion at onset of type 1 diabetes in children without ketoacidosis. Issue 6 (15th April 2018) - Enander, Rebecka; Adolfsson, Peter; Bergdahl, Torun; Forsander, Gun; Ludvigsson, Johnny; Hanas, Ragnar
Abstract : Background: Our aim was to see if IV insulin therapy at diagnosis preserves beta‐cell function better than multiple subcutaneous (SC) injections. Methods: Fifty‐four children 9.9 ± 3.5 years (range 2.8‐14.9) without ketoacidosis were included in a 2 years, randomized multicenter study with insulin SC or 48 to 72 hours IV initially. Thirty‐three (61%) were boys, 22 (41%) were pubertal. Forty‐eight subjects completed 12 months follow‐up and 43 completed 24 months. At 1, 6, 12, and 24 months, hemoglobin A1c (HbA1c), C‐peptide and insulin/kg/24 h were measured. At 24 months, a mixed‐meal tolerance test (MMTT) was performed. Results: HbA1c at diagnosis was 10.7%, (93 mmol/mol) for IV, 10.7%, (94 mmol/mol) for SC. During the first 2 full days of insulin therapy, mean plasma glucose was 8.2 mmol/L for IV, 9.5 for SC ( P = .025). Mean insulin dose was 1.5 U/kg/d for IV vs 1.0 for SC ( P = .001). Sixteen (7 in IV, 9 in SC group) started with insulin pumps during the follow‐up. At 24 months, we saw no significant differences: HbA1c (7.5%, 58 mmol/mol, for IV, 7.2%, 55 mmol/mol, for SC; ns), insulin doses (0.79 vs 0.88 U/kg/d; ns), fasting C‐peptide (0.08 vs 0.12 nmol/L; ns), maximal MMTT response (0.19 vs 0.25 nmol/L; ns) and AUC (18.26 vs 23.9 nmol/L*min; ns). Peak C‐peptide >0.2 nmol/L in the combined IV and SC groups correlated significantly with HbA1c and C‐peptide at onset in a multiple regression. Conclusion: Residual beta cell function at 2 years seems to be independent from initial insulin regimens but related to HbA1c and C‐peptide at onset.